Epiphytic Plants on Stand of Schima wallichii (D.C.) Korth. at Mount Lawu - AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2000)
The objectives of the research were to know: (1) the diversity of epiphyte species at the stand of puspa trees (Schimawallichii (D.C.) Korth.) in Cemoro Sewu and Cemoro Kandang of mount Lawu, and (2) the distribution and cover abundance of the species based on its location from the land surface. The research objects were all species of epiphyte plants on the stand of puspa trees. The procedures of data collection were including species collection in the field, make up herbariums, observation of epiphyte vegetation using transect method and morphology observation in the laboratory. The results show that in the south slope of the mount Lawu were found 23 species of epiphyte consisting 4 species of lichenes, 2 species of Fungi, 3 species of Bryophyte, 10 species of Pterydophyte, 2 species of Orchidaceae and 2 species of liana. The species with the highest density was Bryophyte, and the highest diversity was Pterydophyte. The height of the trees affects the distribution, diversity and density of the epiphyte plants.Â© 2000 Jurusan Biologi FMIPA UNS Surakarta Key words: Schima wallichii (D.C.) Korth., mount Lawu, biodiversity, epiphyte plant.